A plague of prisons : the epidemiology of mass incarceration in America - Drucker, Ernest M., 1940- (New York, NY ; London : The New Press, 2013)
"Drucker (criminal justice, City U. of New York, and epidemiology, Columbia U.) applies public health concepts to compare the structure of modern incarceration systems to epidemics from the past. He describes two classic epidemics--cholera in nineteenth-century London and AIDS in twentieth-century New York--to show how the concept and tools of epidemiology work, and explains the anatomy of a major epidemic; the start of mass incarceration in New York State; how the rates of imprisoned people in recent decades show the features of plagues from previous centuries; the impact of incarceration on individuals, their children, and families; and how imprisonment has become a social issue requiring a public health approach"--(booknews.com).
An epidemiological riddle -- Cholera in London : the ghost maps of Dr. Snow -- AIDS : the epidemiology of a new disease -- A different kind of epidemic -- Anatomy of an outbreak : New York's Rockefeller drug laws and the prison pump -- Orders of magnitude : the relative impact of mass incarceration -- A self-sustaining epidemic : modes of reproduction -- Chronic incapacitation : the long tail of mass incarceration -- The contagion of punishment : collateral damage to children and families of prisoners -- Ending mass incarceration : a public health model -- Afterword to the paperback edition: The future of mass incarceration in America.
Originally published: New York : New Press, 2011; with a new afterword.
Includes bibliographical references (pages 217-243) and index.
Keywords: Imprisonment -- United States; Imprisonment -- Social aspects -- United States; Criminal justice, Administration of -- Social aspects -- United States; Criminal justice, Administration of -- Social aspects; Imprisonment; Imprisonment -- Social aspects; United States